2022
DOI: 10.3389/fenvs.2022.993677
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of airbnb’s green user emotional characteristics: How do human, geographical, housing, and environmental factors influence green consumption?

Abstract: In the context of the sharing economy, green consumption is becoming a trend. Shared accommodation represented by Airbnb has been extensively studied. Analysis of the emotional characteristics of green users is the key to promoting the sustainable development of Airbnb. The article obtains the online reviews of Airbnb green users, fully considers the deviation caused by the weight of feature words to the sentiment calculation, and combines the sentiment value with the weight value to obtain the comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Hence, this research emphasises the fact that host-guest interaction is a key factor influencing sustainable consumption behaviour in shared accommodation and the significance of building up host-guest relations with the green consumer segment. The above findings support previous papers' results [54] by further demonstrating that relationships are more important in the minds of green consumers and that good relationships are more conducive to sustainable consumption behaviour. Meanwhile, the empirical findings support those of previous papers [37,64,101], demonstrating that host-guest interaction is a process of value co-creation and social exchange instead of pure economic reciprocity, which also explains why green consumers value their relationships with hosts and tend to consume more sustainably in the sharing accommodation context.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, this research emphasises the fact that host-guest interaction is a key factor influencing sustainable consumption behaviour in shared accommodation and the significance of building up host-guest relations with the green consumer segment. The above findings support previous papers' results [54] by further demonstrating that relationships are more important in the minds of green consumers and that good relationships are more conducive to sustainable consumption behaviour. Meanwhile, the empirical findings support those of previous papers [37,64,101], demonstrating that host-guest interaction is a process of value co-creation and social exchange instead of pure economic reciprocity, which also explains why green consumers value their relationships with hosts and tend to consume more sustainably in the sharing accommodation context.…”
Section: Discussionsupporting
confidence: 91%
“…The intensifying concerns regarding climate change and its extensive ecological consequences influence consumers to make environmentally responsible purchasing decisions [52]. Individuals identified as 'green consumers' have a high propensity to engage in eco-friendly behaviours [53], and they consistently employ terms relevant to green consumption behaviours in their transactional exchanges [54]. Sustainable consumption behaviours (SCBs) encompass a set of behaviours that contribute to sustainability [55].…”
Section: Green Consumers and Sustainable Consumption Behaviours (Scbs...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Martin conducted a case study on the Danish organic food system and observed that trustworthiness holds particular significance within this system, as higher levels of consumer trust are associated with stronger inclinations toward green consumption ( Martin, 2015 ). As a novel consumption model, green consumption benefits from the enhancement of consumer beliefs regarding products and companies, evoking positive emotions and, consequently, amplifying consumers’ willingness to engage in green consumption ( Wang and Wangt, 2022 ). Trust exercises a pivotal influence on consumers’ selection and implementation of green consumption behaviors, with individuals exhibiting higher levels of trust displaying greater intentions for green consumption.…”
Section: Theoretical Models and Basic Hypothesesmentioning
confidence: 99%